KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH SEBAGAI PEMODERASI PENGARUH KOMPETENSI PROFESIONAL DAN KOMITMEN NORMATIF TERHADAP KINERJA ( STUDI PADA SMP NEGERI SUB RAYON 3 KOTA SEMARANG - Mukaromah, 12.52.02.0180; Indarti, MG Kentris (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study is intended to analyze the influence of professional competence of teachers, and normative commitment of teachers on teacherâs performance with moderation of transformational leadership by school principal. The population of the entire state teachers in state junior high school in sub rayon 3 of Semarang city summed up to 285 people with only 167 people were taken as samples by using Slovin method of sampling. The results of partial analysis of each variable are not significant on professional competence of teachers while normative commitment have not significant effect on the performance of teachers, and principalsâ transformational leadership have not significantly influence the performance of teachers in Junior High School in Sub Rayon 3 of Semarang City. Strong interaction between the professional competence of teachers and principals transformational leadership , can not provide a strong influence also on improving teacher performance, as well as strong interaction between normative commitment of teachers and principals transformational leadership, can not provide a strong influence also on improving teacher performance. Keywords: professional competence of teachers, normative commitment of teachers, teacherâs performance, transformational leadership of principals.